2013
DOI: 10.1038/cdd.2013.159
|View full text |Cite
|
Sign up to set email alerts
|

Jmjd3 is essential for the epigenetic modulation of microglia phenotypes in the immune pathogenesis of Parkinson’s disease

Abstract: Classical activation (M1 phenotype) and alternative activation (M2 phenotype) are the two polars of microglial activation states that can produce either detrimental or beneficial effects in the central nervous system (CNS). Harnessing the beneficial properties of microglia cells by modulating their polarization states provides great potential for the treatment of Parkinson's disease (PD). However, the epigenetic mechanism that regulates microglia polarization remains elusive. Here, we reported that histone H3K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
140
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(158 citation statements)
references
References 44 publications
6
140
1
1
Order By: Relevance
“…Basal and stimulated secretion of TNF-α and IL-6 were increased in the ex vivo culture of senescent microglia [203], and hypertrophic morphological changes in the aged cells were observed [197,204,205]. Consistent with this evidence, an in vivo study showed that iNOS, TNF-α, and IL-6 were elevated, while arginase-1 was repressed in the midbrain of aged mice [206]. In contrast, peripheral macrophages exhibited less classical activation, leading to an attenuated proinflammatory response [207].…”
Section: Agingsupporting
confidence: 56%
“…Basal and stimulated secretion of TNF-α and IL-6 were increased in the ex vivo culture of senescent microglia [203], and hypertrophic morphological changes in the aged cells were observed [197,204,205]. Consistent with this evidence, an in vivo study showed that iNOS, TNF-α, and IL-6 were elevated, while arginase-1 was repressed in the midbrain of aged mice [206]. In contrast, peripheral macrophages exhibited less classical activation, leading to an attenuated proinflammatory response [207].…”
Section: Agingsupporting
confidence: 56%
“…: no significance. microglial M1 and M2 states, such as iNOS, TNF-a, IL-1b and Arg-1, in the presence of stimulus [26,27]. Thus, we used N9 microglia to study microglial M1 and M2 states in this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A number of biological processes could be affected by aging including the ability of mitochondria to handle with calcium, the iron level within neurons, the function of UPS and the activating pattern of microglia and, etc. (Crain et al 2013;Reeve et al 2014;Tang et al 2014). Understandably, these functional changes might weaken the nigral DAergic neurons, rendering the neurons more vulnerable to additional insults (Reeve et al 2014).…”
Section: G2019s Lrrk2 Confers Higher Vulnerability To Lactacystin-indmentioning
confidence: 97%